Relationship between Anxiety Concerning Dementia Onset and Subjective Memory Impairment in Frail Older Individuals - Yukiko Suzuki; Takayuki Sudo; Hideki Mochizuki; Nobuaki Shimoda (Dementia and Geriatric Cognitive Disorders Extra)
Introduction: This study aimed to clarify the relationship between anxiety about the possibility of developing dementia (dementia onset anxiety) and subjective memory impairment in frail older individuals who require long-term care and are experiencing declining cognitive function. Methods: This study included 30 frail older individuals requiring long-term care who completed the Everyday Memory Checklist (EMC), which was simultaneously performed by an occupational therapist (OT). Individuals were divided into two groups: with and without anxiety about dementia onset. We examined the relationship between the presence of anxiety about dementia onset and assessment scores on EMC by the individuals and by the OT. Results: Approximately 40% of participants expressed anxiety about developing dementia. No significant differences existed between the two groups in terms of age, sex, number of years of education, number of ongoing medical conditions under treatment, types of oral medications, Mini-Mental State-Japanese scores, and total functional independence measure scores. Self-assessed EMC scores by the individuals showed a significant difference between the two groups (p = 0.012, φ = 0.41), while no significant difference in the OT-assessed EMC scores. Conclusion: Despite similar levels of objective cognitive decline and objective everyday memory impairment, individuals with anxiety about developing dementia have more severe subjective memory impairment than those without such anxiety.